Big Data and Modernity Challenges: A Required Regulation? - Cravo, Victor (Law, State and Telecommunications Review, 2016)
Purpose ”“ This article introduces the reader to the paradigmatic revolution performed by Big Data, and encourages imagining how jurisprudence and the law can deal with the challenges that will result from modernity of technology. Methodology/approach/design ”“ It was composed from bibliographic research aimed at explaining the Big Data phenomenon and challenging its implications on the law, in light of the theory of Immanuel Wallerstein on modernity. Findings ”“ The main features of the novel phenomenon of Big Data are presented with emphasis on the potential harmful implications for democratic participation in the regulatory process, in order to relate them to the concepts of modernity of technology and modernity of liberation developed by Immanuel Wallerstein. Practical implications ”“ The article serves as an invitation to the researcher interested in the impact of modernity of technology in the legal institutions that modulate and legitimate the regulatory process, with special focus on Big Data. Originality/value ”“ It innovates in the Brazilian legal research to the extent that it assists in delving the implications of Big Data in Portuguese speaking literature.